COMMUNITY SUPERVISION OF PENYANGGA VILLAGES IN THE KHDTK OF GUNUNG BROMO THROUGH HEALTH FOREST DEVELOPMENT - supriyadi; Malihatun Nufus; Manggar Arum Aristri; Selfi Handayani; Ivana Cindy Febrianti (Universitas Pelita Harapan, 2026)
Forest healing is a scientific approach to recovering from physical and mental stress through interaction with nature. Activities include meditation, leisurely walks through the forest or simply listening to the sounds of nature. This practice has proven effective in countries like Japan and Korea. In addition to health benefits such as reducing stress and improving mood, this concept supports forest conservation and economic growth. This is because it raises participants’ awareness of the improtance of preserving forests and boosting the local economy through ecotourism and community empowerment. The KHDTK of Gunung Bromo has significant potential for developing health forest tourism. Therefore, community service was conducted in the form of mentoring the Penyangga villang community (KTH Putri Serang and MPA Singo Serang) to identify and analyze the potential for health forest tourism in the KHDTK of Gunung Bromo and design alternative routes within the health forest footprint to ensure sustainable and adaptive forest management. The community service method used was a participatory rapid appraisal (PRA) approach. Based on the results of the community service activities, the Penyangga village community was enthusiastic about the development of health forests and increased their knowledge regarding health forests.